Enhancing the oxidative stability of algal oil emulsions by adding sweet orange oil: Effect of essential oil concentration. (1st September 2021) - Xu, Na; Wu, Xiaolin; Zhu, Yuqing; Miao, Jinyu; Gao, Yi; Cheng, Ce; Peng, Shengfeng; Zou, Liqiang; Julian McClements, David; Liu, Wei
Highlights: Sweet orange essential oil (SOEO) was added into algal oil emulsion. The algal oil emulsions with different SOEO content have good physical stability. SOEO increases the adsorption capacity of oil–water interface proteins. SOEO can improve the oxidative stability of algal oil emulsion. The algal oil emulsion with 10% SOEO has the best oxidative stability. Abstract: The effects of sweet orange essential oil (SOEO) concentration (0–12.5% of oil phase) on the physical stability, oxidative stability, and interfacial composition of algal oil-in-water emulsions containing sodium caseinate-coated oil droplets was examined. SOEO addition had no influence on the microstructure and physical stability of the algal oil emulsions. The addition of SOEO enhanced the oxidation stability of algal oil emulsion. As an example, the values of algal oil emulsions with 0 and 10% SOEO were 198 and 100 mmol/kg algal oil after 16 days of accelerated oxidation, respectively. The absorbed protein level was higher in the algal oil emulsion containing 10% SOEO (70%) than in 0% SOEO (57%). This result suggested that the presence of SOEO enhanced the interfacial thickness, possibly by interacting with the casein molecules. A thicker protein layer may have helped to retard the oxidation of the omega-3 oils inside lipid droplets.